Citizen Science Identification of Isolated Blue Stellar Systems in the Virgo Cluster - Swapnaneel Dey; Michael G. Jones; David J. Sand; Nicolas Mazziotti; Steven Janowiecki; Gregory R. Zeimann; Paul Bennet (The Astrophysical Journal)
We present a catalog of 34 new candidate (13 high confidence) isolated, young stellar systems within the Virgo galaxy cluster identified through a citizen science search of public optical and ultraviolet imaging. “Blue blobs” are a class of blue, faint, isolated, extremely low stellar mass, and metal-rich star-forming clouds embedded in the hot intracluster medium of the Virgo cluster. Only six blue blobs were known previously and here we confirm an additional six of our candidates through velocity and metallicity measurements from follow-up optical spectroscopy on the Hobby–Eberly Telescope (HET). Our 13 high confidence candidates (including the six confirmed) have properties consistent with prior known blue blobs and are inconsistent with being low-mass galaxies. Most candidates are concentrated in relatively dense regions, roughly following filamentary structures within the cluster, but avoiding its center. Three of our candidates are likely the stellar counterparts of known “optically dark” clouds of neutral hydrogen in the cluster, while a further four are widely separated extensions to previously known blue blobs. The properties of our new candidates are consistent with previous conclusions that blue blobs likely originated from ram pressure stripping events, however, their locations in velocity–projected cluster-centric radius phase space imply that their parent galaxies are not on their first infall into the cluster. Through our ongoing follow-up program with HET we aim to confirm additional candidates, however, detailed understanding of the stellar populations and star formation histories of blue blobs will require JWST observations.